The impact of a pneumococcal conjugate vaccination program on the nasopharyngeal carriage, serotype distribution and antimicrobial resistance of Streptococcus pneumoniae among healthy children in Turkey - KEPENEKLİ KADAYİFCİ, EDA; ALTINKANAT GELMEZ, GÜLŞEN; HASDEMİR GÖKBOĞA, MÜNEVVER UFUK; BORAN, PERRAN (ELSEVIER SCI LTD, 2016)
Background: The 7-valent conjugate pneumococcal vaccine (PCV7) was introduced by the Turkey National Immunization Program in 2008 and replaced by the PCV13 in 2011. We assessed the impact of PCV vaccination on the nasopharyngeal (NP) carriage, serotype distribution and antimicrobial resistance of Streptococcus pneumoniae (SP) among healthy Turkish children. Methods: A prospective surveillance study was performed between September 2011 and September 2013 in Istanbul, Turkey. NP swabs, demographic data, and vaccination statuses were obtained from 2165 healthy children aged 0-18 years. Pneumococcal carriage was defined by a positive culture; serotyping was performed via multiplex conventional PCR, and the antibiotic susceptibilities of the isolates were determined based on the minimum inhibitory concentration (MIC) values of the Clinical Laboratory Standards Institute (CLSI). Results: The prevalence of pneumococcal carriage was 6.4%. The carriage rates were 8%, 7%, and 5% in the following age groups: 0-24 months, 25-60 months, and >60 months, respectively. The carriage rate was significantly higher in the 0-24 month age group than in the >60 months age group (p = 0.03). Sixty percent of the children were not vaccinated with any PCV; 4%, 2%, and 4% received at least 1, 2 or 3 doses and 30% children received the full schedule (4 doses) of either PCV7 or PCV13. Among the isolated S. pneumoniae strains, 45% were of the non-vaccine type (NVT) and 55% were of the vaccine type (VT). The children who received at least a single PCV dose had significantly lower odds of colonization via VT serotypes than the non-vaccinated children [odds ratio: 0.61 (95% confidence interval = 0.41-0.91), p = 0.01]. The percentages of the serotypes covered by PCV7 and PCV13 were 51% and 56%, respectively. The most frequently isolated serotypes were 6A/B/C (n = 22, 16.5%), 19F (n = 18, 13.5%), 23F (n = 15, 11.2%), serotype 9V/A (n = 10, 7.5%), 12F (n = 5, 4.5%), 15A/F (n = 7, 4.5%) and 22 A/F (n = 6, 4.5%). Using the meningitis criteria and the MIC, 62% of the isolates were resistant to penicillin and 13% were non sensitive to ceftriaxone. Erythromycin and clindamycin resistance were 43% and 31%, respectively. Conclusion: We shown that following nation-wide PCV vaccination, S. pneumoniae NP carriage was decreased. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: S. pneumoniae; Nasopharyngeal carriage; Post-vaccination; Healthy children; Turkey; TURKISH CHILDREN; YOUNG-CHILDREN; ANTIBIOTIC-RESISTANCE; HONG-KONG; PCR; COLONIZATION; EMERGENCE; VACCINES